Beyond Oil: A Political Economy Perspective on Azerbaijan’s Growth Model - Sariyeva, Aliya (My University, 2026)
This paper analyzes the development of Azerbaijan’s economic growth model from a political economy perspective, focusing on the role of state institutions, oil revenues, and elite strategies. It tests the argument that the current model of the country is more accurately described as a hybrid of administrative Keynesianism and state capitalism. Six key phases of economic and political development are covered from the initial postSoviet years to the post-Covid period. Relying on macroeconomic data, institutional reports, and sectoral trends, the study reveals that growth is primarily state-driven and heavily reliant on hydrocarbon exports. Despite developed policy initiatives aimed at diversification, structural dependence and limited private sector capacity persist. The findings suggest that without right institutional reform, Azerbaijan’s development path will remain vulnerable to external shocks and dependent on government redistribution.
Keywords: Political economy -- Azerbaijan.; Economic development -- Azerbaijan.; State capitalism -- Azerbaijan.; Keynesian economics -- Azerbaijan.